Empowering Virtual Reality as a Learning Media: A Real Environment to Exploring User Experience - Diky Al Khalidy; Syamsul Bachri; Sumarmi; Sugeng Utaya; Alfyananda Kurnia Putra; Batchuluun Yembuu (Postgraduate, University of Mataram, 2025)
This study aimed to explore students' experiences with VR Geopark Ijen as a learning media for physical environment material, examining the factors influencing these experiences. Employing a survey methodology at Zainul Hasan 1 Senior High School, the sample comprised 82 students from the 11th grade. Data collection involved closed and open-ended questionnaires, with analysis conducted using descriptive statistics based on mean scores. Qualitative data from student responses provided deeper insights into the quantitative findings. Results indicated that VR Geopark Ijen provided a positive and significant experience for students. They rated the media as very good criteria across multiple aspects, including usefulness, pleasantness, entertaining, productivity, novelty, reliability, efficiency, user-friendliness, attractiveness, enjoyment, fulfilment, meaningfulness, engagement, communicativeness, collaborativeness, helpfulness, convincingness, willingness, and recommend. Aspects of feature comprehensiveness, confidence, attentiveness, responsiveness, respectfulness received good criteria. VR Geopark Ijen effectively facilitated contextual and meaningful learning, increased active student engagement, and delivered an enjoyable experience. These findings suggest that VR Geopark Ijen has the potential to be an innovative solution for improving the quality of physical environment learning, addressing access limitations and enhancing student understanding. Further development should consider feature comprehensiveness, bolster student confidence, and integrate VR with the curriculum while providing teacher training.